Loss of zinc-finger protein 212 leads to Purkinje cell death and locomotive abnormalities with phospholipase D3 downregulation - Rin Khang (Nature Portfolio, 2021)
Abstract Although Krüppel-associated box domain-containing zinc-finger proteins (K-ZNFs) may be associated with sophisticated gene regulation in higher organisms, the physiological functions of most K-ZNFs remain unknown. The Zfp212 protein was highly conserved in mammals and abundant in the brain; it was mainly expressed in the cerebellum (Cb). Zfp212 (mouse homolog of human ZNF212) knockout (Zfp212-KO) mice showed a reduction in survival rate compared to wild-type mice after 20 months of age. GABAergic Purkinje cell degeneration in the Cb and aberrant locomotion were observed in adult Zfp212-KO mice. To identify genes related to the ataxia-like phenotype of Zfp212-KO mice, 39 ataxia-associated genes in the Cb were monitored. Substantial alterations in the expression of ataxin 10, protein phosphatase 2 regulatory subunit beta, protein kinase C gamma, and phospholipase D3 (Pld3) were observed. Among them, Pld3 alone was tightly regulated by Flag-tagged ZNF212 overexpression or Zfp212 knockdown in the HT22 cell line. The Cyclic Amplification and Selection of Targets assay identified the TATTTC sequence as a recognition motif of ZNF212, and these motifs occurred in both human and mouse PLD3 gene promoters. Adeno-associated virus-mediated introduction of human ZNF212 into the Cb of 3-week-old Zfp212-KO mice prevented Purkinje cell death and motor behavioral deficits. We confirmed the reduction of Zfp212 and Pld3 in the Cb of an alcohol-induced cerebellar degeneration mouse model, suggesting that the ZNF212–PLD3 relationship is important for Purkinje cell survival.